(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the effect of differentiated learning model assisted by Plotagon application on students’ numeracy literacy skills on the material of System of Linear Equations Two Variables (SPLDV). The research method used was quasi-experimental with Posttest-Only Control Design. The research population included all students of class VIII SMP Negeri 17 Pontianak in the academic year 2024/2025. The sample selection was conducted through cluster random sampling technique, which determined class VIII G as the experimental class that received differentiated learning with the help of Plotagon application, and class VIII E as the control class that only received differentiated learning. Data analysis was conducted using t-test to compare the learning outcomes of both groups. The results showed significant differences. The average numeracy literacy score in the experimental class reached 80 (very good), much higher compared to the control class which only obtained an average of 70.60 (good). The t-test proved that there is a significant difference, namely that the numeracy literacy ability of students taught with differentiated learning assisted by the Plotagon application is better than the numeracy literacy ability of students taught with differentiated learning alone on the system of linear equations with two variables material in grade VIII of SMP Negeri 17 Pontianak.